SUATU KETERKAITAN ANTARA KEHENDAK TUHAN DAN PERENCANAAN MANUSIA: KAJIAN HERMENEUTIKA AMSAL 19:21 - Leonardo Israel Mamesah; Farel Yosua Sualang (Institut Agama Kristen Negeri Manado, 2026)
This article discusses the relationship between God's will and human planning with a focus on Proverbs 19:21 through a literary wisdom hermeneutical approach. This verse affirms that although many plans are in the heart of man, it is God's decision that will be carried out. Previous studies have generally highlighted God's sovereignty dogmatically or emphasized the practical aspects of human planning, but rarely integrated the two within a comprehensive hermeneutical framework. This research gap forms the basis for this study to present a new analysis. The research uses qualitative methods with semantic analysis of the Hebrew text and a review of classical and contemporary theological literature. The results of the study show three connections between humans and God: decision-making as a form of ethical responsibility, a corrective framework through God's involvement in directing plans, and evaluation of the final results as God's final decision. Thus, this study confirms that human planning and God's will are not two mutually exclusive poles, but complement each other. Proverbs 19:21 provides an ethical-theological basis for believers to plan their lives with wisdom, humility, and surrender amid the complexities of the modern world.